Управління товарно-матеріальними запасами виробничого цеху за допомогою abc- та xyz-аналізу - Уманська, К. Д.; Колесник, О. Б. (ХНУРЕ, 2025)
Effective inventory management minimizes costs and enhances logistics in manufacturing. This study applies ABC and XYZ analysis to classify inventory by value and consumption stability. Traditional models like EOQ and JІТ are reviewed, highlighting their strengths and limitations. Integrating ABC-XYZ analysis optimizes procurement and reduces stock imbalances. The study also explores automation and ERP systems for better control. Results show improved efficiency and adaptability, with future research focusing on AI-driven predictive analytics for smarter inventory management.
Keywords: управління запасами; товарний запас; виробничий цех